Pengaruh Pola Asuh Orang Tua terhadap Motivasi Belajar Siswa Kelas V SDN 2 Temulus Pada Masa Pandemi Covid-19 - Ahmad Sudi Pratikno; Clodia Cindi Aurora; Isna Ida Mardiyana (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The purpose of this study was to determine the description of parenting styles and learning motivation of fifth-grade students at SDN 2 Temulus and to determine whether there is an influence of parenting styles on the learning motivation of fifth-grade students at SDN 2 Temulus. This study uses a quantitative approach. The sample in this study used a saturated sampling technique, which took the entire population as a sample with a total of 28 fifth-grade students. The data collection technique used questionnaires and documentation, the data collection instrument used a parent and student questionnaire sheet, and the data analysis technique used quantitative analysis using the SPSS application. The results showed that the parenting style mostly used by fifth-grade parents at SDN 2 Temulus was democratic parenting with a percentage of 82%. The percentage of learning motivation of fifth-graders at SDN 2 Temulus is mostly in the "good" category as much as 39%. Based on the results of the linearity test, indicating that the significance value obtained is 0.856 > 0.05, it can be concluded that there is a significant relationship between the parenting style variable (X) on student motivation (Y). Based on the SPSS calculation output, the calculated F value is 0.546 < F_table 0.553 so it can be concluded that Ha is accepted and Ho is rejected. This means that there is an influence of parenting patterns on the learning motivation of fifth-graders at SDN 2 Temulus during the Covid-19 pandemic.